1963
DOI: 10.1530/acta.0.0420348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adrenal Steroids on Radio-Calcium Metabolism in Young Beagle Dogs

Abstract: The influence of 9α-fluoro,16α-methylprednisolone, 6α-fluoroprednisolone, and 6α-methylprednisolone on 47Ca utilization was studied in young beagle dogs. The major effect of steroid therapy, with each dog as his own control, is to increase 47Ca eliminated in the faeces and urine. Based on mean treated/control ratios 9α-fluoro,16α-methylprednisolone causes 2.5 to 10 times more inhibition of utilization of radio-calcium than equivalent doses of 6α-fluoroprednisolone or 6α-methylprednisolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

1970
1970
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
14
2
Order By: Relevance
“…Moreover, the results of the flux studies conducted in the chamber leave little doubt that cortisone administration affects the active component of the intestinal calcium transport system. The fact that the transmural electric potential differences during the steady state as well as the calcium fluxes noted in the present study were lower than those previously reported by others (26), may reflect the use of fructose rather than glucose as substrate and the presence of a higher (4 It would appear that the mucosa of the distal small intestine is relatively impermeable to calcium, and the permeability barrier may be dependent upon oxidative metabolism. In the present studies, the administration of cortisone to vitamin D-repleted animals enhanced the transport of calcium and strontium in ileal gut sacs incubated under 02 in vitro.…”
Section: Methodscontrasting
confidence: 72%
See 2 more Smart Citations
“…Moreover, the results of the flux studies conducted in the chamber leave little doubt that cortisone administration affects the active component of the intestinal calcium transport system. The fact that the transmural electric potential differences during the steady state as well as the calcium fluxes noted in the present study were lower than those previously reported by others (26), may reflect the use of fructose rather than glucose as substrate and the presence of a higher (4 It would appear that the mucosa of the distal small intestine is relatively impermeable to calcium, and the permeability barrier may be dependent upon oxidative metabolism. In the present studies, the administration of cortisone to vitamin D-repleted animals enhanced the transport of calcium and strontium in ileal gut sacs incubated under 02 in vitro.…”
Section: Methodscontrasting
confidence: 72%
“…Similar results were noted with strontium, which, while less well transported than calcium, does seem to share a common vitamin D-dependent transport mechanism (28 The animals were maintained on the standard diet, adequate in vitamin D. Gut sacs were prepared from the proximal 5 cm of duodenum and the terminal 5 cm of ileum. In experiments 1 and 2, everted sacs were filled with 0.5 ml of a medium containing 0.151 M NaCI, 4.0 X 10-3 M sodium phosphate buffer at pH 7.4, and 2.0 X 102-M fructose. In experiment 1, the sacs were bathed in 4.0 ml of a similar medium which contained, in addition, 3.0 X 10-3 M BaC12 and 133Ba (10,200 cpm/0.1 ml of medium).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 5 (21), rats (20), and dogs (22), although in our study dexamethasone did not alter colonic Ca secretion. The data of Ferretti et al (21) may explain, at least in part, the divergent findings on the effect of glucocorticoids on intestinal Ca absorption.…”
Section: Resultscontrasting
confidence: 42%
“…Pharmacologic doses of corticosteroids impair intestinal absorption of calcium (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and result in a negative calcium balance (4,(9)(10)(11), which may contribute to the development of osteoporosis. It has been postulated that corticosteroids decrease intestinal calcium absorption either by interfering with the metabolic activation of vitamin D or by antagonizing, directly or indirectly, the effects of vitamin D on the gut, or by both mechanisms (12).…”
Section: Introductionmentioning
confidence: 99%